A statewide 3D geological model for New South Wales. Issue 1 (1st December 2019) - Stolz, Edward; Spampinato, Giovanni; Davidson, John
Summary: The Geological Survey of New South Wales is building a statewide 3D geological model comprising a series of interlocking province-scale models and a 3D statewide fault network. The model is being developed in conjunction with the New South Wales Seamless Geology geodatabase and is constrained by mapped geology, interpreted geology, drillhole intersections, seismic sections and potential-field imagery and modelling. Detailed 3D models of mineral, hydrocarbon, coal and groundwater resources will be embedded within the framework provided by the statewide 3D model. The model will support land use management, mineral and energy exploration, scientific research, groundwater management, civil engineering and other applications.